Retinoic Acid-Induced 2 (RAI2) Is a Novel Antagonist of Wnt/β-Catenin Signaling Pathway and Potential Biomarker of Chemosensitivity in Colorectal Cancer - Zhang, Weitao; Kong, Lu; Zhu, Hongbin; Sun, Decong; Han, Quanli; Yan, Bin; Cui, Zhi; Zhang, Weiwei; Zhang, Shurong; Kang, Xindan; Dai, Guanghai; Qian, Niansong; et al. (Frontiers in Oncology, 2022)
Objective: Aberrant activation of Wnt/β-catenin signaling contributes to maintenance of cancer stem cells and chemoresistance in colorectal cancer (CRC). Retinoic acid-induced 2 (RAI2) was proved to be a tumor suppressor in CRC in our previous report. In this study, the role of RAI2 in Wnt/β-catenin signaling was further investigated. Methods: As a transcriptional co-regulator, C-terminal Binding Protein 2 (CtBP2) was reported to be involved in Wnt signaling in multiple and complex ways. The correlation of RAI2 and CtBP2 in CRC was analyzed by TCGA dataset, and the interaction between RAI2 and CtBP2 was explored by co-immunoprecipitation (CoIP) in CRC cells. The effect of RAI2 on activity of Wnt signaling and the location of β-catenin were detected by Dual-Luciferase reporter assay and Immunofluorescence respectively. Western blotting analysis was performed to detect the expression of target genes involved in Wnt signaling. Sphere formation assay was employed to detect effect of RAI2 on stem cell like properties. Cell viability assay was used to detect the chemosensitivity of cells before and after transfection of RAI2. Results: The interaction between RAI2 and CtBP2 was confirmed by CoIP in CRC cells. Besides, negative correlation of RAI2 and CtBP2 in CRC was found by analyzing TCGA dataset. Re-expression of RAI2 in human colon cancer cells (HCT116 and LoVo) suppressed the fluorescent activity of Wnt signaling, increased the phosphorylation and inhibited nuclear translocation of β-catenin, with down-regulation of target genes like c-myc, cyclinD1, ASCL2 and LGR5. In contrast, the mutated RAI2, which can’t interact with CtBP2, has no above effects. We observed low expression of RAI2 in 33.89% (101/298) of CRC patients, which was significantly associated with reduced phosphorylation of β-catenin (r=0.8866, P＜0.0001), poor 5-year relapse-free survival (RFS) (P = 0.0029) and overall survival (OS) (P = 0.0102). Restoration of RAI2 in RKO and LoVo cells inhibited stem cell-like properties of CRC cells and increased chemosensitivity of these cells to oxaliplatin and fluorouracil. Conclusion: As an independent poor prognostic marker, RAI2 inhibits Wnt signaling by interacting with or down-regulating CtBP2, resulting in repression of stem cell-like properties and increased chemosensitivity of CRC cells.